Environmental NGOs in China - partners in environmental governance - Dorit Lehrack (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2006)
This paper is a snapshot of the potential of Chinese environmental NGOs1 to effectively address environmental problems and needs, alone and in partnership with others. As environmental NGOs have only be on stage for the last ten years or so and as they undergo dynamic changes, a thoroughly conducted scientific analysis about the strengths, weaknesses, opportunities and risks is not possible yet. However, as the author has more than six years working experience with different Chinese environmental NGOs across the country, some empiric findings can be given, and some trends and tendencies be predicted. The paper starts with a look at the history of NGOs in China with a specific focus on environmental NGOs, followed by problems and chances caused by the present legal status of the groups. It then describes the main working areas of Chinese environmental NGOs, illustrating them by giving some representative examples. After a brief analysis, the paper proposes current trends and tendencies about the development of China's environmental NGOs. The main trend is that Chinese NGOs, independently on their origin (grass root, semistate organizations or Government-organized non-profit environmental organizations) will gain more respect and influence in both environmental awareness raising and as competent partners in policy formulation and law enforcement, if the State institutions concerned will involve them in planning and developing processes in an early stage and assist them in their capacity building.
Keywords: 300